Capacidad de respuesta del DLQI y la versión colombiana validada del Skindex-29 en alopecia cicatricial y no cicatricial (2024)
ABSTRACT: Alopecia is a frequent reason for consultation. It has a negative impact on quality of life (QOL). However, studies with patients more kind of alopecia are lacking. This study evaluated QOL and sensitivity to change of the Skindex-29 and the DLQI in these. This was an observational study with a longitudinal design, including two measurements over time and prospective data. It was carried out in four outpatient centers in Medellín, between 2023 and 2024. We included sociodemographic and clinical data, as well as the DLQI and Skindex-29 quality of life questionnaires before and after treatment. Participation of women was 51%; the most frequent types of alopecia were androgenic alopecia (52%), alopecia areata (AA) (19%) and telogen effluvium (TE) (9%). The alopecia types with the greatest impact on QOL (pretreatment) measured through the DLQI and the Skindex-29, respectively, were TE [10.29 (±9.32) and 40.39 (±32.04)], AA [9.27 (±9.13) and 33.91(±26.47)], dissecting cellulitis [8.67(±8.33) and 29.6(±15.33)] and lichen planus pilaris [6.75(±6.55) and 6.75(±6.55)]. In conclusion, the version validated in Colombia of the Skindex-29 and the Colombian Spanish version of the DLQI showed a moderate responsiveness when evaluating the QOL of patients with scarring and non-scarring alopecia, before and after starting specific treatment.